Glass fiber composite coated board paper with high tensile strength and preparation method of glass fiber composite coated board paper
By using composite materials of high alkali glass fiber and synthetic chemical fiber, the problems of insufficient mechanical strength and unsatisfactory porosity in the production of lead-acid battery grids are solved, and the coated paper with high tensile strength and good breathability are achieved, which improves production efficiency and product quality.
Patent Information
- Application Number
- CN202411957522.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
In the production of lead-acid battery grids, traditional board coated paper has problems such as insufficient mechanical strength, difficulty in controlling thickness, water absorption, and unsatisfactory pore size distribution and porosity.
The composite materials of high alkali glass fiber and synthetic chemical fiber are used to improve the mechanical properties of glass fibers through dispersion and etching treatment, and the composite coated paper with high tensile strength is prepared through appropriate slurry treatment and drying steps.
It significantly improves the mechanical strength and breathability of the coated paper, ensures the uniformity and consistency of the coated board process, reduces material waste, and improves the production efficiency and product quality of lead-acid battery grids.
Smart Images

Figure CN119800762A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-acid batteries, in particular to a high-tensile strength glass fiber composite coated paper and a preparation method thereof. Background Art
[0002] As one of the important chemical power sources, lead-acid batteries have developed rapidly in various application fields, but there are also serious environmental pollution phenomena in the production process. Compared with the current domestically common "gravity casting grid" manufacturing process, the expanded (mesh drawing), punching, continuous casting and rolling grid manufacturing processes are "clean production technologies for lead-acid battery plates". The process of this new technology is: first, the lead ingots are made into continuous lead strips through the "lead strip continuous casting and rolling" technology, and then the grids are made through the "continuous mesh (punching) technology" or "mesh drawing technology", and then the lead paste is applied by a double-sided plate coating machine, and finally the lead-acid battery grids are made. This technology mainly involves cold processing (except for melting lead). The molten lead is precisely controlled in a temperature range close to the melting point (327-340°C), and then rapidly cooled to obtain a crystallized and refined metal structure. Subsequent continuous rolling, mesh drawing, punching and other processing processes are all carried out at room temperature. The implementation of this process avoids the use of high temperatures and stirring of the molten lead, and does not produce lead smoke and lead slag, thereby completely blocking possible lead smoke emissions and greatly reducing energy consumption and lead consumption.
[0003] The application scope of continuous grid production processes such as mesh drawing, continuous casting and pressing, and continuous punching is getting wider and wider, and these methods have become the mainstream in the production of automotive batteries. In the process of continuous grid coating, it is generally necessary to use coating paper. The main function of the paper is to attach to both sides of the plate during coating to prevent the lead paste from falling off and sticking to the equipment, and to prevent the plates from sticking to each other when stacked.
[0004] Traditional coated paper has some shortcomings in terms of performance, such as insufficient mechanical strength, difficulty in controlling thickness within an ideal range, water absorption problems, and unsatisfactory pore size distribution and porosity. In order to meet the needs of industrial production and application, it is necessary to develop a coated paper with high tensile strength, thinness and toughness, non-water absorption, uniform pore size distribution and high porosity. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a high tensile strength glass fiber composite coated paper and a preparation method thereof, which solves the problems raised by the above-mentioned background technology.
[0007] (II) Technical solution
[0008] To achieve the above objectives, the present invention is implemented through the following technical scheme: A high tensile strength glass fiber composite coated paper comprises the following components in parts by weight: 92-100 parts of high alkali glass fiber and 0-8 parts of synthetic chemical fiber.
[0009] Preferably, the high tensile strength glass fiber composite coated paper comprises the following components in parts by weight: 100 parts of high alkali glass fiber.
[0010] Preferably, the high tensile strength glass fiber composite coated paper comprises the following components in parts by weight: 95 parts of high alkali glass fiber and 5 parts of synthetic chemical fiber.
[0011] Preferably, the high tensile strength glass fiber composite coated paper comprises the following components in parts by weight: 92 parts of high alkali glass fiber and 8 parts of synthetic chemical fiber.
[0012] Preferably, the synthetic fiber comprises the following components in parts by weight: 1-2 parts of nylon staple fiber, 2-3 parts of polyester fiber, and 2-3 parts of spandex fiber.
[0013] Preferably, the high-alkali glass fiber has a diameter of 2-15 μm and a length of 3-30 mm.
[0014] Preferably, the thickness of the composite coated paper is 0.15-0.17 mm.
[0015] The present invention further discloses a method for preparing a high tensile strength glass fiber composite coated paper, based on the high tensile strength glass fiber composite coated paper as described above, comprising the following steps:
[0016] Step 1: Raw material dispersion:
[0017] Dispersing high-alkali glass fibers and synthetic chemical fibers to prepare a suspension slurry;
[0018] Step 2: Preparation and molding:
[0019] The suspended slurry is pulped through a mesh screen and then dried to obtain a composite coated paper.
[0020] The present invention further discloses a method for preparing a high tensile strength glass fiber composite coated paper, based on the high tensile strength glass fiber composite coated paper as described above, comprising the following steps:
[0021] Step 1: Proper corrosion:
[0022] The high-alkali glass fiber is dispersed, and then placed in a mixed acid solution and etched at 70-80° C. for 4-5 hours to obtain a suspension slurry; wherein the mixed acid solution is a mixture of 0.3-0.4 mol / L H2SO4 and 0.3-0.4 mol / L HCL in a volume ratio of 1:1-2;
[0023] Step 2: Preparation and molding:
[0024] The above-mentioned suspended slurry is fully washed with water until the pH value is neutral, and then pulped with a mesh screen and dried to obtain a composite coated board paper.
[0025] Preferably, in step 1, the dispersion speed is 80-120 rpm, and the dispersion time is 20-40 minutes; in step 2, the drying temperature is 80-100°C.
[0026] (III) Beneficial effects
[0027] The present invention provides a high tensile strength glass fiber composite coated paper and a preparation method thereof, which has the following beneficial effects:
[0028] 1. The mechanical strength of the coated paper is significantly improved, making it less likely to break during the production of lead-acid battery grids, thereby improving production efficiency and product quality; and by precisely controlling the thickness of the coated paper, the uniformity and consistency of the coating process is ensured, reducing material waste.
[0029] 2. Use weak alkaline solution to corrode the glass fiber appropriately. Under the premise of not affecting the mechanical properties of a single glass fiber, the roughness of the glass fiber surface is increased, thereby increasing the friction between the glass fibers, thereby improving the mechanical properties of the glass fiber coated paper; secondly, the uniform pore size distribution and high porosity make the coated paper have good air permeability in the production of lead-acid battery grids, which is beneficial to the curing of lead paste and the improvement of battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the preparation method of Embodiment 3, Embodiment 4, Embodiment 5 and Embodiment 6 of the present invention;
[0031] Figure 2 It is a schematic diagram of the preparation method flow of Example 1 and Example 2 of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Embodiment 1:
[0034] The embodiment of the present invention provides a high tensile strength glass fiber composite coated paper, the composite coated paper has a thickness of 0.15 mm and comprises the following components by weight: 100 parts of high alkali glass fiber. Specifically, the high alkali glass fiber has a diameter of 5 μm and a length of 10 mm.
[0035] like Figure 2 As shown, an embodiment of the present invention further provides a method for preparing a high tensile strength glass fiber composite coated paper, based on the high tensile strength glass fiber composite coated paper as described above, comprising the following steps:
[0036] Step 1: Proper corrosion:
[0037] The high-alkali glass fiber is dispersed, and then placed in a mixed acid solution and etched at 70° C. for 4 hours to obtain a suspension slurry; wherein the mixed acid solution is a mixture of 0.3 mol / L H2SO4 and 0.3 mol / L HCL in a volume ratio of 1:1;
[0038] Step 2: Preparation and molding:
[0039] The above-mentioned suspended slurry is fully washed with water until the pH value is neutral, and then pulped with a mesh screen and dried to obtain a composite coated board paper.
[0040] Embodiment 2:
[0041] The difference between this embodiment and the first embodiment is that Figure 2 As shown, an embodiment of the present invention further provides a method for preparing a high tensile strength glass fiber composite coated paper, based on the high tensile strength glass fiber composite coated paper as described above, comprising the following steps:
[0042] Step 1: Proper corrosion:
[0043] The high-alkali glass fiber is dispersed, and then placed in a mixed acid solution and etched at 80° C. for 5 hours to obtain a suspension slurry; wherein the mixed acid solution is a mixture of 0.4 mol / L H2SO4 and 0.4 mol / L HCL in a volume ratio of 1:2;
[0044] Step 2: Preparation and molding:
[0045] The above-mentioned suspended slurry is fully washed with water until the pH value is neutral, and then pulped with a mesh screen and dried to obtain a composite coated board paper.
[0046] Embodiment three:
[0047] The embodiment of the present invention provides a high tensile strength glass fiber composite coated paper, the composite coated paper has a thickness of 0.16 mm, and includes the following components by weight: 95 parts of high alkali glass fiber and 5 parts of synthetic chemical fiber. The synthetic chemical fiber includes the following components by weight: 1 part of nylon staple fiber, 2 parts of polyester fiber, and 2 parts of spandex fiber; secondly, the diameter of the high alkali glass fiber is 10 μm and the length is 20 mm.
[0048] like Figure 1 As shown, an embodiment of the present invention further provides a method for preparing a high tensile strength glass fiber composite coated paper, based on the high tensile strength glass fiber composite coated paper as described above, comprising the following steps:
[0049] Step 1: Raw material dispersion:
[0050] The high-alkali glass fiber and the synthetic chemical fiber are dispersed at a speed of 80 rpm and a dispersion time of 20 minutes to prepare a suspension slurry;
[0051] Step 2: Preparation and molding:
[0052] The above suspension slurry is slurried through a mesh screen and then dried at a drying temperature of 80° C. to obtain a composite coated paper.
[0053] Embodiment 4:
[0054] The difference between this embodiment and the third embodiment is that in step one, the dispersion speed is 120 rpm and the dispersion time is 40 minutes; in step two, the drying temperature is 100°C.
[0055] Embodiment five:
[0056] The embodiment of the present invention provides a high tensile strength glass fiber composite coated paper, the composite coated paper has a thickness of 0.17 mm, and includes the following components by weight: 92 parts of high alkali glass fiber and 8 parts of synthetic chemical fiber. The synthetic chemical fiber includes the following components by weight: 2 parts of nylon staple fiber, 3 parts of polyester fiber, and 3 parts of spandex fiber; secondly, the diameter of the high alkali glass fiber is 15 μm and the length is 30 mm.
[0057] like Figure 1 As shown, an embodiment of the present invention further provides a method for preparing a high tensile strength glass fiber composite coated paper, based on the high tensile strength glass fiber composite coated paper as described above, comprising the following steps:
[0058] Step 1: Raw material dispersion:
[0059] The high-alkali glass fiber and the synthetic chemical fiber are dispersed at a speed of 80 rpm and a dispersion time of 20 minutes to prepare a suspension slurry;
[0060] Step 2: Preparation and molding:
[0061] The above suspension slurry is slurried through a mesh screen and then dried at a drying temperature of 80° C. to obtain a composite coated paper.
[0062] Embodiment six:
[0063] The difference between this embodiment and the fifth embodiment is that in step one, the dispersion speed is 120 rpm and the dispersion time is 40 minutes; in step two, the drying temperature is 100°C.
[0064] Comparative Example:
[0065] A composite coated paper, the composite coated paper has a thickness of 0.15 mm and comprises 100 parts of high alkali glass fiber. Specifically, the high alkali glass fiber has a diameter of 5 μm and a length of 10 mm.
[0066] The preparation method of the composite coated paper is based on the composite coated paper as described above, and comprises the following steps:
[0067] Step 1: Raw material dispersion:
[0068] Dispersing high alkali glass fiber at a speed of 80 rpm and for 20 minutes to obtain a suspension slurry;
[0069] Step 2: Preparation and molding:
[0070] The above suspension slurry is slurried through a mesh screen and then dried at a drying temperature of 80° C. to obtain a composite coated paper.
[0071] Experimental example:
[0072] The properties of the composite coated paper prepared in Examples 1 to 6 and the comparative example were tested, and the results are shown in the following table:
[0073]
[0074] According to the above table, the tensile strength of the composite coated paper of Examples 1 to 6 is higher than that of the composite coated paper of the comparative example, which indicates that the composite coated paper of the present invention has higher strength and better mechanical properties. In addition, the moisture content of the embodiments is lower than that of the comparative example, indicating that the composite coated paper of the present invention has better waterproof performance. In terms of porosity, the porosity of the embodiments is higher than that of the comparative example, which may be because the diameter and length of the glass fiber in the composite coated paper of the present invention are moderate, so that the coating has better air permeability. Based on the above performance test results, the composite coated paper of the present invention is superior to the traditional composite coated paper in terms of strength, waterproofness and air permeability, and meets the beneficial effects of high tensile strength glass fiber composite coated paper.
[0075] In summary, the high tensile strength glass fiber composite coated paper prepared by the present invention not only has a significant improvement in tensile strength, but also exhibits excellent performance in terms of waterproofness and air permeability. This makes the composite coated paper have a wider application prospect in a variety of applications, such as in the fields of building decoration, packaging materials, and automotive interiors. Its excellent physical properties and chemical stability make it an ideal substitute for traditional composite coated paper. In addition, the preparation method of the present invention is simple and efficient, and is easy to realize industrial production, providing new technical options and economic benefits for related industries.
[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high tensile strength glass fiber composite coated paper, characterized in that: The invention comprises the following components in parts by weight: 92-100 parts of high-alkali glass fiber and 0-8 parts of synthetic chemical fiber.
2. The high tensile strength glass fiber composite coated paper according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 100 parts of high-alkali glass fiber.
3. The high tensile strength glass fiber composite coated paper according to claim 1, characterized in that: The invention comprises the following components by weight: 95 parts of high-alkali glass fiber and 5 parts of synthetic chemical fiber.
4. The high tensile strength glass fiber composite coated paper according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 92 parts of high-alkali glass fiber and 8 parts of synthetic chemical fiber.
5. The high tensile strength glass fiber composite coated paper according to claim 3 or 4, characterized in that: The synthetic chemical fiber comprises the following components by weight: 1-2 parts of nylon staple fiber, 2-3 parts of polyester fiber, and 2-3 parts of spandex fiber.
6. The high tensile strength glass fiber composite coated paper according to claim 1, characterized in that: The high-alkali glass fiber has a diameter of 2-15 μm and a length of 3-30 mm.
7. The high tensile strength glass fiber composite coated paper according to claim 1, characterized in that: The thickness of the composite coated paper is 0.15-0.17 mm.
8. A method for preparing high tensile strength glass fiber composite coated paper, based on the high tensile strength glass fiber composite coated paper according to claim 1, characterized in that: The following steps are involved: Step 1: Raw material dispersion: Dispersing high-alkali glass fibers and synthetic chemical fibers to prepare a suspension slurry; Step 2: Preparation and molding: The suspended slurry is pulped through a mesh screen and then dried to obtain a composite coated paper.
9. A method for preparing high tensile strength glass fiber composite coated paper, based on the high tensile strength glass fiber composite coated paper according to claim 1, characterized in that: The following steps are involved: Step 1: Appropriate corrosion: The high-alkali glass fiber is dispersed, and then placed in a mixed acid solution and etched at 70-80° C. for 4-5 hours to obtain a suspension slurry; wherein the mixed acid solution is a mixture of 0.3-0.4 mol / L H2SO4 and 0.3-0.4 mol / L HCL in a volume ratio of 1:1-2; Step 2: Preparation and molding: The above-mentioned suspended slurry is fully washed with water until the pH value is neutral, and then pulped with a mesh screen and dried to obtain a composite coated board paper.
10. The method for preparing a high tensile strength glass fiber composite coated paper according to claim 8 or 9, characterized in that: In step 1, the dispersion speed is 80-120 rpm, and the dispersion time is 20-40 minutes; in step 2, the drying temperature is 80-100°C.